Adaptation of "New Normal" to Marine Ecotourism Activities and Their Impact on the Welfare of Coastal Communities - Andaki , Jardie A.; Aling, Djuwita R.R.; Rantung, Steelma V. (Jurnal Ilmiah Platax, 2023)
Abstract This study aims to find out how the adaptation to the new normal period in the marine ecotourism business and its influence on coastal communities in West Likupang District. The research was conducted in West Likupang District in 4 villages (Bahoi, Bulutui, Tarabitan, and Jayakarsa). The survey method was used to collect primary and secondary data. Quantitative data obtained in this study were obtained from respondent questionnaire data which were processed using the Microsoft Excel 2010 program. The data were also processed by cross-tabulation and statistically analyzed using the statistical t test using SPSS 16.0 For Windows software. The t statistical test (t-test) is used to test differences in ecotourism conditions before the pandemic, the Covid-19 pandemic, and the new normal period. The results of data analysis using the t-test statistic showed a significant difference in the boat transportation business (P<0.05) with a decrease of 75%; homestay (P<0.05) with a decrease of 93%; a number of visits (P<0.05) with a decrease of 63%; and culinary (P<0.05) with a decrease of 67%. A qualitative assessment shows that the Covid-19 pandemic has caused a reduction in the frequency of work from the community in the form of tour guides, dive guides, fishing activity guides, parking attendants, motorcycle taxi drivers, bathroom guards, and ticket guards. A further implication of reduced visits is in the form of cessation of services from several jobs so that workers in the ecotourism sector adapt by diversifying jobs to be able to support their families and themselves.   Keywords: covid-19, ecotourism, new normal, community welfare  Abstrak Penelitian ini bertujuan untuk mengetahui bagaimana adaptasi pada masa new normal pada usaha ekowisata bahari dan pengaruhnya pada masyarakat pesisir di Kecamatan Likupang Barat. Penelitian dilaksanakan di Kecamatan Likupang Barat pada 4 (empat) desa (Bahoi, Bulutui, Tarabitan, dan Jayakarsa). Metode survey digunakan untuk pengumpulan data primer dan sekunder. Data kuantitatif yang diperoleh pada penelitian ini diperoleh merupakan data hasil kuesioner responden yang diolah dengan menggunakan program microsoft excel 2010. Data juga diolah dengan tabulasi silang dan dianalis secara statistik dengan uji statistik t menggunakan software SPSS 16.0 For Windows. Uji statistik t (t test) ini digunakan untuk menguji perbedaan kondisi ekowisata sebelum masa pandemi, masa pandemi covid-19, dan masa new normal. Hasil analisis data dengan statistik uji t menunjukkan perbedaan signifikan pada usaha transportasi perahu (P<0,05) dengan penurunan sebesar 75%; home stay (P<0,05) dengan penurunan sebesar 93%; jumlah kunjungan (P<0,05) dengan penurunan sebesar 63%; dan kuliner (P<0,05) dengan penurunan sebesar 67%. Penilaian secara kualitatif menunjukkan masa pandemic covid-19 menyebabkan berkurangnya frekuensi pekerjaan dari masyarakat berupa tour guide, dive guide, pemandu kegiatan pemancingan, tukang parkir, tukang ojek, penjaga kamar mandi, dan penjaga karcis. Implikasi lebih jauh dari berkurang kunjungan berupa penghentian layanan jasa dari beberapa pekerjaan sehingga masyarakat pekerja di bidang ekowisata beradaptasi dengan melakukan diversifikasi pekerjaan untuk dapat menafkahi keluarga dan diri sendiri. Kata kunci: covid-19, ekowisata, normal baru, kesejahteraan masyarakat